2017
DOI: 10.1515/euco-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Rural Tourism – Evaluating the Quality of Destination

Abstract: This paper concerns the topic of rural destination quality from the viewpoint of tourism development. The research exploring crucial quality factors from the viewpoint of demand is presented. Rural tourism participants attribute the highest significance to Destination cleanliness and Sense of security. The evaluation of the importance of most research quality factors is not dependent on gender and on the contrary, the importance of 16 quality factors depends on the visitor´s age. In the case of the factor of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(28 reference statements)
3
10
0
3
Order By: Relevance
“…The last dimension 3: transportation was completely removed from the final model due to its unimportance; in other words, no significant influence on satisfaction nor loyalty was revealed. This fact corresponds with the previous research of the authors [57].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The last dimension 3: transportation was completely removed from the final model due to its unimportance; in other words, no significant influence on satisfaction nor loyalty was revealed. This fact corresponds with the previous research of the authors [57].…”
Section: Resultssupporting
confidence: 93%
“…This dimension has the largest impact on satisfaction and concurrently it is also the most influential in loyalty towards the destination of all the dimensions. This fact corresponds with the results mentioned by Meng et al [56]-as well as with the results of the previous research of the authors [57]-where this dimension was evaluated as the most important from the viewpoint of evaluating the destination quality factors' significance by the visitors themselves. All the relevant factors (F15, F14, F12, F13, F10) stayed in the model as significant indicators of this dimension, which proves the fact that all the factors have an important impact on creating the dimension of well-being.…”
Section: Resultssupporting
confidence: 91%
“…The research destination quality factors used in the survey were chosen on basis of authors previous empirical research (Ryglová et al, 2017; 2018) adopted with wine destination type. The primary data have been obtained by online questionnaire among Czech respondents and at the same time visitors of wine destination, where the questions regarding the satisfaction and importance of quality factors were formulated using five-point Likert scale (number five represents the highest significance/satisfaction of/with an individual factor).…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies carried out in various industries using SERVPERF (banks, pest control, laundry, wine tourism, fast food chain, restaurant) [60][61][62][64][65][66][67], found a superior performance in terms of satisfaction assessment than of using other service evaluation tool. Taking into consideration that SERVPREF has a reduced a number of survey itemsonly 22 items altogether-the studies have demonstrated its superiority in relation to the SERVQUA.…”
Section: Satisfaction and The Servperfmentioning
confidence: 99%